Factors influencing purchase intention of cloud-based food delivery - Karmawan, I. Gusti Made; Dwitahthea Susanto, Irenea Jessica; Gui, Anderes; Muhammad Shabir, Shaharudin; Fernando, Yudi; Ikhsan, Ridho Bramulya (Institute of Electrical and Electronics Engineers Inc., 2021)
The development of technology makes a lot of changes including in the culinary field. Cloud-based food delivery is increasingly used especially in Indonesia. The objective of this research is to find factor influencing purchase intention. The research model was assessed by using SmartPLS from 209 participants who using cloud based delivery food which collect using google form. Therefore, this research was made to find out if the system quality, information quality, service quality of the application affects the user satisfaction of the cloud based food delivery. Seeing the influence of user satisfaction on perceived net benefit and the influence of perceived net benefit on purchase intention with loyalty programme membership as moderation variable. The result show all the hypotheses supported except system quality not positive impact to user satisfaction. To get more purchase intention, marketplace of cloud-based food delivery need to increase user satisfaction, give more benefit for customer and continuous loyalty programme.